Forest response to increasing typhoon activity on the Korean peninsula: evidence from oak tree-rings - Altman, Jan; Doležal, Jiří; Cerný, Tomáš; Song, Jong-Suk (Global change biology, 2013)
The globally observed trend of changing intensity of tropical cyclones over the past few decades emphasizes the need for a better understanding of the effects of such disturbance events in natural and inhabited areas. On the Korean Peninsula, typhoon intensity has increased over the past 100 years as evidenced by instrumental data recorded from 1904 until present. We examined how the increase in three weather characteristics (maximum hourly and daily precipitation, and maximum wind speed) during the typhoon activity affected old-growth oak forests. Quercus mongolica is a dominant species in the Korean mountains and the growth releases from 220 individuals from three sites along a latitudinal gradient (33-38°N) of decreasing typhoon activity were studied. Growth releases indicate tree-stand disturbance and improved light conditions for surviving trees. The trends in release events corresponded to spatiotemporal gradients in maximum wind speed and precipitation. A high positive correlation was found between the maximum values of typhoon characteristics and the proportion of trees showing release. A higher proportion of disturbed trees was found in the middle and southern parts of the Korean peninsula where typhoons are most intense. This shows that the releases are associated with typhoons and also indicates the differential impact of typhoons on the forests. Finally, we present a record of the changing proportion of trees showing release based on tree-rings for the period 1770-1979. The reconstruction revealed no trend during the period 1770-1879, while the rate of forest disturbances increased rapidly from 1880 to 1979. Our results suggest that if typhoon intensity rises, as is projected by some climatic models, the number of forest disturbance events will increase thus altering the disturbance regime and ecosystem processes.
Keywords: cyklonové bouře; dub (rod); Republic of Korea; Korejská republika; stromy; Trees; Quercus; Cyclonic Storms